COVID-19—A Novel Zoonotic Disease: A Review of the Disease, the Virus, and Public Health Measures. (May 2020) - Mackenzie, John S.; Smith, David W.
A cluster of cases of pneumonia of unknown etiology emerged in Wuhan, China, at the end of December 2019. The cluster was largely associated with a seafood and animal market. A novel Betacoronavirus was quickly identified as the causative agent, and it is shown to be related genetically to SARS-CoV and other bat-borne SARS-related Betacoronaviruses . The number of cases increased rapidly and spread to other provinces in China, as well as to another four countries. To help control the spread of the virus, a "cordon sanitaire " was instituted for Wuhan on January 23, 2020, and subsequently extended to other cities in Hubei Province, and the outbreak declared a Public Health Emergency of International Concern by the Director General of the World Health Organization on January 30, 2020. The virus was named SARS-CoV-2 by the International Committee for the Taxonomy of Viruses, and the disease it causes was named COVID-19 by the World Health Organization. This article described the evolution of the outbreak, and the known properties of the novel virus, SARS-CoV-2 and the clinical disease it causes, and the major public health measures being used to help control it's spread. These measures include social distancing, intensive surveillance and quarantining of cases, contact tracing and isolation, cancellation of mass gatherings, and community containment. The virus is the third zoonotic coronavirus, after SARS-CoV and MERS-CoV, but appears to be the only one with pandemic potential. However, a number of important properties of the virus are still not well understood, and there is an urgent need to learn more about its transmission dynamics, its spectrum of clinical severity, its wildlife origin, and its genetic stability. In addition, more research is needed on possible interventions, particularly therapeutic and vaccines.